Exergy Efficiency Promotion for the System of CO2 Hydrogenation to Methanol in Habitable Confined Space - Xiong, Kai; Yin, Yong-Li; Cao, Yong; Liu, Xiao-Tian (Frontiers in Energy Research, 2021)
Excess hydrogen and carbon dioxide will be produced during the operation of life support system in habitable confined spaces (HCS), to eliminate the two excess gases by converting them into methanol is of great significance for maintenance of atmospheric balance and protection of crew’s life safety. Due to the limited energy supply ability within HCS, it is important for the system of carbon dioxide hydrogenation to methanol (CDHM) to operate with high energy efficiency to reduce unnecessary external energy consumption and internal energy loss. In this paper, exergy analysis method is adopted for exergy efficiency improvement. Specifically, parametric study on the exergetic performance of the CDHM system is conducted based on the three key working condition parameters that have a huge impact on the reaction process and energy utilization quality, which is used to find the favorable working condition with low external energy consumption and exergy destruction per unit gas elimination and high exergy efficiency. Within the chosen three reaction parameters which are reaction pressure, temperature, and space velocity ranging from 5 to 8MPa, from 483.15 to 543.15K, and from 2800 to 4000h-1 respectively, the gases elimination of carbon dioxide and hydrogen increase by 13.3%, 19.58%, and 30.58%, respectively. Moreover, the input power, cold energy consumption, and exergy destruction per molar synthetic methanol all grow to some extent, leading to a 0.06% decline, a 0.46% promotion, and a 0.15% decrease, respectively in the exergy efficiency. The results show that the high exergy efficiency can be realized with relatively low pressure, high temperature, and low space velocity in the working condition. Besides, the exergy destructions of each components in the CDHM system are also presented in this paper. The exergy destructions in the methanol synthesis reactor, heater, and heat exchanger hot end are found to be the three biggest, which summation accounts for more than 90% of the total system exergy destruction. Thus, the exergy efficiency also can be improved by reducing the three biggest exergy destructions.